Predictors of poor mental and physical health status among patients with chronic hepatitis C infection: The Chronic Hepatitis Cohort Study (CHeCS). Issue 3 (30th January 2015) - Boscarino, Joseph A.; Lu, Mei; Moorman, Anne C.; Gordon, Stuart C.; Rupp, Loralee B.; Spradling, Philip R.; Teshale, Eyasu H.; Schmidt, Mark A.; Vijayadeva, Vinutha; Holmberg, Scott D.; ,
Abstract : Our objective was to assess the extent and risk factors for depression and poor physical health among patients with chronic hepatitis C virus (HCV) infection. We surveyed HCV‐infected patients seen at four large healthcare systems participating in the Chronic Hepatitis Cohort Study (CHeCS). Survey data included demographics, depression and physical health measures, substance use history, current social support, recent stressor exposures, and, from the electronic medical record, treatment history, and Charlson Comorbidity Index scores. There were 4, 781 respondents, who were a mean of 56.7 years old, 71% White, and 57% male. Altogether, 51.4% reported past injection drug use, 33.9% were current smokers, and 17.7% had abused alcohol in the previous year. Additionally, 47.4% had been previously treated for HCV and 14.8% had a 12‐week sustained viral response (SVR) following HCV therapy. Overall, 29.7% of patients met criteria for current depression and 24.6% were in poor physical health. In multivariate analyses, significant predictors of depression and poor health included: male gender (versus female, odds ratios [ORs], 0.70 and 0.81), Black race (versus white, ORs, 0.60 and 0.61), having education less than high school (versus college, ORs, 1.81 and 1.54), being employed (versus not, ORs, 0.36 and 0.25), having high life stressors (versus low, ORs, 2.44 and 1.64), having low social support (versus high, ORs = 2.78 and 1.40), and having high Charlson scores (versus none, ORs = 1.58 and 2.12). Achieving a 12‐week SVR was found to be protective for depression. Conclusion : This large survey of U.S. HCV patients indicates the extent of adverse health behaviors and mental and physical comorbidities among these patients. (Hepatology 2015;61:802–811)